Preference and reinforcer efficacy of high‐ and low‐tech items: A comparison of item type and duration of access. Issue 2 (9th March 2017) - Hoffmann, Audrey N.; Samaha, Andrew L.; Bloom, Sarah E.; Boyle, Megan A.
Abstract : This study examined the interactions of stimulus type (high‐ vs. low‐tech) and magnitude (duration of access) on preference and reinforcer efficacy. Two preference assessments were conducted to identify highly preferred high‐tech and low‐tech items for each participant. A subsequent assessment examined preference for those items when provided at 30‐s and 600‐s durations. We then evaluated reinforcer efficacy for those same items when provided for a range of durations using progressive‐ratio schedules. Results suggested item type and access duration interacted to influence preference and reinforcer efficacy. Participants preferred high‐tech items at longer durations of access and engaged in more responding when the high‐tech item was provided for long durations, but these patterns were reversed for the low‐tech item. In addition, participants engaged in less responding when the high‐tech item was provided for short durations and when the low‐tech item was provided for long durations.